Advances in the national inertial fusion program of China - He X.T.; Zhang W.Y. (EPJ Web of Conferences, 2013)
The planned inertial confinement fusion (ICF) ignition in China in around 2020 is to be accomplished in three steps. The first is carrying out target physics experiments in the existing laser facilities SG-II, SG-IIIP and SG-IIU (operating in 2012) of output energy 3-24 kJ at 3ω. Results have been obtained for better understanding the implosion dynamics and radiation transport. Recent studies include efficiency of radiation generation, hydrodynamic instabilities, shock waves in cryogenic targets, opacity measurements using kJ lasers, etc. Hydrodynamic codes (the LARED series) have been developed and experimentally verified with over 5000 shots, and are applied to investigating target physics and ignition target design. For fast ignition, a large number of experiments and numerical simulations have led to improved understanding relevant to target design, hot electron transport, collimation by the spontaneous magnetic fields in overdense plasmas, etc. In addition to the SG-II, SG-IIU and SG-IIIP, the SG-III laser facility with energy of 200–400 kJ at 3ω shall operate in 2014 and be used for advanced target physics research. In the last step, the 1.5 MJ SG-IV laser facility still under design will be used to investigate ignition and burning.